1999
DOI: 10.1111/j.1600-0757.1999.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral ecology and person‐to‐person transmission of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis

Abstract: The ecological characteristics of the oral cavity are dissimilar for A. actinomycetemcomitans and for P. gingivalis, as judged by differences in their colonization preferences and patterns, associations with periodontal disease parameters, relationships with the subgingival microbiota and the type of periodontitis and their clonal persistence in the oral cavity. These features also suggest that as a periodontal pathogen, A. actinomycetemcomitans is different from P. gingivalis. Probably in most infected indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 148 publications
8
113
1
4
Order By: Relevance
“…Accordingly, Paster et al (2001) found the species only once; Sakamoto et al (2000) did not find it at all in their clone populations. Furthermore, culture studies of Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans showed that Actinobacillus actinomycetemcomitans occurs in lower proportions than Porphyromonas gingivalis (see review by Asikainen & Chen, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Paster et al (2001) found the species only once; Sakamoto et al (2000) did not find it at all in their clone populations. Furthermore, culture studies of Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans showed that Actinobacillus actinomycetemcomitans occurs in lower proportions than Porphyromonas gingivalis (see review by Asikainen & Chen, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The Gram-negative, capnophilic bacterium Actinobacillus actinomycetemcomitans, a member of the family Pasteurellaceae, is implicated as a major causative agent of localized aggressive periodontitis and other forms of periodontitis (Asikainen & Chen, 1999;Slots, 1999). A. actinomycetemcomitans is naturally competent for transformation (Fujise et al, 2004;Tønjum et al, 1990;Wang et al, 2002Wang et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In industrialized countries, oral colonization by A. actinomycetemcomitans is most commonly monoclonal (4). Additionally, spontaneous or treatment-induced changes in an A. actinomycetemcomitans clone(s) are rare in individuals persistently culture positive for the species (24; W. Z. Chen, S. Rich, and C. Chen.…”
mentioning
confidence: 99%